Predicting Adolescent Dating Violence Perpetration: Role of Exposure to Intimate Partner Violence and Parenting Practices - Latzman, Natasha E. (Am J Prev Med, 2015)
INTRODUCTION: Exposure to adult intimate partner violence (IPV) places youth at risk for a range of outcomes, including perpetration of adolescent dating violence (ADV). However, there is variability in the effect of IPV exposure, as many youth who are exposed to IPV do not go on to exhibit problems. Thus, research is needed to examine contextual factors, such as parenting practices, to more fully explain heterogeneity in outcomes and better predict ADV perpetration. The current research draws from a multisite study to investigate the predictive power of IPV exposure and parenting practices on subsequent ADV perpetration. METHODS: Participants included 417 adolescents (48.7% female) drawn from middle schools in high-risk, urban communities. IPV exposure, two types of parenting practices (positive parenting/involvement and parental knowledge of their child’s dating), and five types of ADV perpetration (threatening behaviors, verbal/emotional abuse, relational abuse, physical abuse, and sexual abuse) were assessed at baseline (2012) and approximately 5 months later (2013) via adolescent report. Analyses (conducted in 2015) used a structural equation modeling approach. RESULTS: Structural models indicated that IPV exposure was positively related only to relational abuse at follow-up. Further, adolescents who reported parents having less knowledge of dating partners were more likely to report perpetrating two types of ADV (physical and verbal/emotional abuse) at follow-up. Analyses did not demonstrate any significant interaction effects. CONCLUSIONS: Results fill a critical gap in understanding of important targets to prevent ADV in middle school and highlight the important role that parents may play in ADV prevention